2001
DOI: 10.1073/pnas.171211398
|View full text |Cite
|
Sign up to set email alerts
|

Activation and autoregulation of DNA-PK from structured single-stranded DNA and coding end hairpins

Abstract: DNA-dependent protein kinase (DNA-PK) acts through an essential relationship with DNA to participate in the regulation of multiple cellular processes. Yet the role of DNA as a cofactor in kinase activity remains to be completely elucidated. For example, although DNA-PK activity appears to be required for the resolution of hairpin coding ends in variable diversity joining recombination, kinase activity remains to be demonstrated from hairpin ends or other DNA structures. In the present study we report that DNA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
32
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 40 publications
2
32
1
Order By: Relevance
“…In the presence of ssDNA, substrate phosphorylation occurs in competition with DNA-PK autophosphorylation and autoinactivation [30]. Previously we demonstrated that this potent autoinactivation of DNA-PK linked in cis can be minimized when assessing phosphorylation of heterologous DNA-PK substrates by performing the kinase reactions at the limiting ATP concentration of 40 nM [30].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In the presence of ssDNA, substrate phosphorylation occurs in competition with DNA-PK autophosphorylation and autoinactivation [30]. Previously we demonstrated that this potent autoinactivation of DNA-PK linked in cis can be minimized when assessing phosphorylation of heterologous DNA-PK substrates by performing the kinase reactions at the limiting ATP concentration of 40 nM [30].…”
Section: Resultsmentioning
confidence: 99%
“…Preliminary studies indicated the phosphorylation of p53 by DNA-PK was dramatically enhanced by the colocalization of p53 to the ssDNA [30]. In the present study we have performed a detailed analysis of the phosphorylation of p53 in the presence of ssDNA.…”
mentioning
confidence: 83%
See 3 more Smart Citations